Excess Volatility and the Credibility Challenges of Fundamentalist Investors - DAVANNE, OLIVIER (Bankers, Markets & Investors, 2025)
Three key variables determine the fair value estimated by fundamentalist investors for financial assets: current and future payoffs, current and future short-term interest rates set by central banks, and current and future excess returns (short-term risk premia) required by investors. While current payoffs and interest rates are observable, short-term risk premia remain private information. Despite the availability of some survey data, fundamentalist investors often make errors in estimating this elusive variable. This study examines the theoretical and empirical implications of such errors. We demonstrate how misjudging short-term risk premia can erode the credibility of fundamentalist investors and amplify volatility. A deeper understanding of the underlying market failures—stemming from private information and bounded rationality—could help these investors better utilize available data and contribute to greater market stability. Bull-markets are born on pessimism, grow on skepticism, mature on optimism and die on euphoria. Sir John Templeton, Founder of Templeton Mutual Funds